Speaker Park : om ljudsättning av utemiljöer - Risberg, Ulf (SLU/Dept. of Urban and Rural Development, 2008)
This project will search for the sound in the contemporary landscape architecture, an attempt to combine music and landscaping. In a first stage, I have searched for outdoor environments where loudspeakers are used, and sites with a concious sound design. The project will result in a sound design created for the park Frodeparken in Uppsala, Sweden.